Gender-transformative Bandebereho Couples' Intervention to Promote Male Engagement in Reproductive and Maternal Health and Violence Prevention in Rwanda : Findings from a Randomized Controlled Trial - Doyle, Kate; Levtov, Ruti G.; Baker, Gary; Bastian, Gautam G.; Bingenheimer, Jeffrey B.; Kazimbaya, Shamsi; Nzabonimpa, Anicet; Pulerwitz, Julie; Sayinzoga, Felix; Sharma, Vandana; Shattuck, Dominick (PLoS, 2018)
Rigorous evidence of the effectiveness of male engagement interventions, particularly on how these interventions impact relationship power dynamics and women’s decision-making, remains limited. This study assessed the impact of the Bandebereho gender-transformative couples’ intervention on impact on multiple behavioral and health-related outcomes influenced by gender norms and power relations. We conducted a multi-site randomised controlled trial in four Rwandan districts with expectant/current fathers and their partners, who were randomised to the intervention (n = 575 couples) or control group (n = 624 couples). Primary outcomes include women’s experience of physical and sexual IPV, women’s attendance and men’s accompaniment at ANC, modern contraceptive use, and partner support during pregnancy. At 21-months post-baseline, 1123 men and 1162 partners were included in intention to treat analysis. Generalized estimating equations with robust standard errors were used to fit the models.